Green Chemistry: Current State and Future Opportunities - N. Al-Darkazali, Waleed; M. Abdallah, Bassam (Al-Nahrain Journal of Science, 2025)
Nowadays, there is no singular solution to all environmental issues; however, green chemistry, also referred to as clean chemistry, represents a fundamental strategy for pollution prevention. This approach offers a transformative perspective on various challenges associated with industrial chemical activities. Historically, industrialists and chemists have focused on minimizing exposure to hazards by managing toxic substances at every stage of the process, including usage, treatment, and disposal. The primary objective of green chemistry is to develop innovative processes that provide economic advantages over traditional methods, thereby encouraging their adoption within the industry. This discipline addresses the challenges of sustainable development by promoting practices that protect the environment and conserve natural resources. Ultimately, while green chemistry does not resolve all environmental problems, it remains a crucial approach for fostering a cleaner environment and ensuring the sustainability of our planet's resources.